Willingness to pay for local food?: Consumer preferences and shopping behavior at Otago Farmers Market. (September 2017) - Berg, Nathan; Preston, Kate L.
Abstract: New Zealand (NZ) survey data from Otago Farmers Market (OFM) provide new expenditures-based measures of local food preference. Discounts applied by consumers to non-local food items (e.g., from USA, China, or elsewhere in NZ) are reported. Some consumers have lexicographic preferences; they are unwilling to purchase non-local food at any price. Others are willing to substitute non-local for local food when priced appropriately. Tobit and Fractional Probit models describe how consumer characteristics affect willingness to pay (WTP) for local food. The mean consumer's premium in WTP when a produce item is "local" ranges from 2.1 to 8.0% and is positively associated with age and income.